American Dream. - Jillson, Calvin C. (American political thought, 2016)
"Cal Jillson discusses the importance and changing meaning of the American Dream in our politics and culture. He uses political, social science, and literary texts to better understand what the American Dream has meant and what its limitations have been. It extends the discussion through the presidency of Barack Obama as well as the work of authors like Jonathan Franzen and economist Thomas Piketty. The author contends that while politicians are willing to speak freely about the American Dream, through literature we better understand the limitations of this dream for most Americans"--